EVALUASI KOMPETENSI GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM 2013 - Mafidapuspadina Mafidapuspadina; Hilal Mahmud; Nilam Permatasari Munir (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
The article discusses about The Evaluation of Teacher Competence in implementing Kurikulum 2013 in Mathematics learning in Senior High School of Palopo. The approach of this research was descriptive quantitative with evaluative research type. The population of this research were all of the Mathematics teachers in Senior High School of Palopo school year 2018/2019 consists of 6 schools with 32 teachers. Technique of Mathematics teacher sampling used purposive sampling. This research specializes in the second grade of these 6 schools because they implemented Kurikulum 2013 only in the second grade. The results showed that assesment of themselves by 15 Mathematics teachers in implementing Kurikulm 2013 in learning proccess were pedagogical competence was 53% placing in “very good” category and 47% placing in “good” category, personality competance was 93% placing in “very good” category and 7% placing in “good” category, social competance was 87% placing in “good” category and 13% placing in “very good” category, and professional competance was 80% placing in “good” category and 20% placing in “very good” category. This suggest that teacher competancies provided by teachers of the second grade of Senior High School of Palopo school year 2018/2019 were in very good category.